SARUNG SEBAGAI SIMBOL IDENTITAS SANTRI: KAJIAN SEMANTIK DI MA’HAD BAITUL ARQOM AL ISLAMI - RAHMAH, NENENG FARIDA (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to examine the symbolic meaning of the sarong as a representation of santri identity at Ma’had Baitul Arqom Al Islami through a semantic approach. The sarong is understood not merely as traditional clothing, but as a cultural sign embedded with rich cultural, religious, and social meanings within pesantren life. Using the library research method, this study explores literature related to semantic theory, cultural symbols, and the construction of santri identity. The analysis shows that denotatively, the sarong functions as a piece of cloth to cover the body. However, connotatively, the sarong represents values of simplicity, equality, obedience, and Islamic piety—core principles in the life of a santri. The sarong also plays a crucial role in constructing collective identity within the pesantren, reinforcing the continuity of local values rooted in the Islamic tradition of the Nusantara. Thus, the meaning of the sarong reflects the integration between cultural expression and character formation within the traditional Islamic education system.